PCR‐free blood group genotyping using a nanobiosensor. Issue 2 (3rd December 2014) - Brouard, D.; Ratelle, O.; Perreault, J.; Boudreau, D.; St‐Louis, M.
<x xml:space="preserve">Abstract</x> Background and Objectives The last two decades have seen major developments in genotyping assays to facilitate the procurement of red blood cell units to alloimmunized patients. To make genotyping faster, simpler and less costly, a nanotechnology approach based on metal/silica fluorescent nanoparticles and a polymer‐based hybridization optical transducer was designed. The objectives of this study were (1) to verify whether this nanobiosensor has the ability to discriminate single nucleotide polymorphisms in non‐amplified genomic DNA and (2) to establish whether the signal generated by the nanobiosensor is sufficiently intense to be detected by standard flow cytometry. Materials and Methods Silver‐core silica‐shell fluorescent nanoparticles (Ag@SiO2) were prepared, and amine‐modified DNA probes were grafted to their surface. A cationic conjugated polymer was electrostatically bound to the surface probes to become optically active upon hybridization with a target. Two nanobiosensor formulations specific to DO*01 and DO*02 alleles were prepared. DNA was extracted from whole blood and mixed with the nanobiosensor for hybridization. The nanobiosensor fluorescence was measured by flow cytometry. Results Nine volunteers were typed for Dombrock blood group antigens DO*01 and DO*02. A statistically significant increase in the optical transduction signal was observed for sequence‐specific samples. All nine genotypes were correctly identified when compared to standardized PCR assays. Conclusion The nanobiosensor provides rapid and simple genotyping of blood group antigens from unamplified genomic DNA and can be measured using standard flow cytometers. This PCR‐free approach could be applied to any known genetic polymorphism.